Instructional strategies for students with mild, moderate, and severe intellectual disability - Bouck, Emily C.; Gargiulo, Richard M. (SAGE Publications, Inc., 2018)
Key Features • Involves not only a focus on elementary, secondary education and transition but also preschool education as well. • Addresses the whole spectrum of students with intellectual disabilities including mild, moderate and severe intellectual disability. • A discussion of assistive technology throughout the chapters reflects technology's increased usage to support students with intellectual disability. • Chapters have been written by leading experts in the respective content